Scalable Integration of Highly Uniform MnxCo3−xO4 Nanosheet Array onto Ceramic Monolithic Substrates for Low‐Temperature Propane Oxidation. Issue 21 (10th October 2017) - Tang, Wenxiang; Ren, Zheng; Lu, Xingxu; Wang, Sibo; Guo, Yanbing; Hoang, Son; Du, Shoucheng; Gao, Pu‐Xian
Abstract: The redox reaction between KMnO4 and Co(NO3 )2 was designed and readily utilized for the scalable integration of spinel Mn x Co3− x O4 nanosheet arrays in three‐dimensional ceramic honeycombs by controlling the reaction temperature. The Co 2+ can reduce MnO4 − to form Mn–Co spinel oxide nanosheet arrays uniformly on the channel surface of cordierite honeycomb. The novel platinum group metal free oxide nanosheet array integrated ceramic honeycomb monolith shows good low‐temperature catalytic activity for propane oxidation, with the 50 % conversion temperature achieved at 310 °C, which is a much lower temperature than that over the wash‐coated commercial Pt/Al2 O3 . These integrated Mn–Co composite oxide nanoarrays may hold great promise for the construction of advanced monolithic catalyst for high‐performance and low‐cost emission control. Abstract : Effective honeycomb coating : The reaction between Co 2+ and MnO4 − is a facile strategy for the integration of Mn–Co composite oxide nanosheet arrays onto the 3 D cordierite honeycomb substrate. The well‐defined structural characteristics and distribution allow effective mass transport and enable improved reaction chemistry and kinetics.